2022
DOI: 10.1001/jamanetworkopen.2022.39803
|View full text |Cite|
|
Sign up to set email alerts
|

Transitions in Health Insurance During the Perinatal Period Among Patients With Continuous Insurance Coverage

Abstract: ImportanceAlthough health insurance continuity is important during the perinatal period to improve birth outcomes and reduce maternal morbidity and mortality, insurance disruptions are common. However, little is known about insurance transitions among insurance types for individuals who remained insured during the perinatal period.ObjectiveTo examine insurance transitions for birthing individuals with continuous insurance, including those with Medicaid and Medicaid managed care coverage, before, during, and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…In contrast, this study used repeated measures of the payer billed at the time of care delivery and/or payment, which removes issues of self‐report and historical recall, and also provides longitudinal data to directly document insurance discontinuity. Perhaps for this reason, our estimate of insurance churn is closer in magnitude to findings from a recent study (14.4%) using the Massachusetts All‐Payer Claims Database to classify insurance transitions in the 12 months before delivery among those with continuous insurance (e.g., transitions between private insurance and Medicaid) 20 …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In contrast, this study used repeated measures of the payer billed at the time of care delivery and/or payment, which removes issues of self‐report and historical recall, and also provides longitudinal data to directly document insurance discontinuity. Perhaps for this reason, our estimate of insurance churn is closer in magnitude to findings from a recent study (14.4%) using the Massachusetts All‐Payer Claims Database to classify insurance transitions in the 12 months before delivery among those with continuous insurance (e.g., transitions between private insurance and Medicaid) 20 …”
Section: Discussionsupporting
confidence: 72%
“…Studies using cross-sectional and self-reported data have reported the presence of insurance discontinuities during pregnancy, 8,9,12,13,19 and one study has used provider-recorded longitudinal data to enumerate transitions in continuous insurance. 20 Our study is the first to use provider-recorded longitudinal data that includes uninsured individuals to detail the timing and nuances of insurance churn. We report a lower prevalence of insurance churn (16.6%) than previous work that used MEPS-HC (58%) 8 or PRAMS (30.1% 9 and 48.7% 19 ) data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found 96% of mothers cited accepting their health insurance plan as a major factor when choosing a prenatal care provider and birth hospital [18,19]. Understanding inclusion of providers and overlap among Medicaid ACOs is particularly important given ongoing transitions in insurance plans, including among those insured by Medicaid, during the perinatal period [20]. Obstetrician-gynecologists (OB/GYNs) are uniquely placed as physicians because they provide preventive services and act as primary care providers for some patients and 25% of women consider their OB/GYN to be their primary care provider; however, they do not always provide the full range of preventive services offered by family physicians and internists, and have not been used to build primary care-focused ACOs [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The sentence should state “Among individuals who transitioned from Medicaid, 64.3% switched to Medicaid managed care.” The article has been corrected. 1 …”
mentioning
confidence: 99%